2016
DOI: 10.1021/acs.chemmater.6b00623
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Exchange Coupled Core|Shell Nanoparticles with High Magnetic Anisotropy: A Strategy toward Rare-Earth-Free Permanent Magnets

Abstract: Antiferromagnetic­(AFM)|ferrimagnetic­(FiM) core|shell (CS) nanoparticles (NPs) of formula Co0.3Fe0.7O|Co0.6Fe2.4O4 with mean diameter from 6 to 18 nm have been synthesized through a one-pot thermal decomposition process. The CS structure has been generated by topotaxial oxidation of the core region, leading to the formation of a highly monodisperse single inverted AFM|FiM CS system with variable AFM-core diameter and constant FiM-shell thickness (∼2 nm). The sharp interface, the high structural matching betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 68 publications
5
107
0
1
Order By: Relevance
“…In addition to its potential spintronics applications [107,108], EB is an important tool in understanding fundamental nanoscale spin ordering, knowledge of which is essential to tailor the anisotropic magnetic properties of nanoparticle systems for potential rare-earth-free permanent magnet applications [109] and for biomedical applications such as magnetic hyperthermia [42,110,111,112] via a controllable exchange coupling mechanism. In particular, Lee et al have shown that the effective anisotropy can be tuned by using exchange-coupled core/shell nanoparticles (exchange anisotropy), which, in effect, increase the heating efficiency of MNPs [110].…”
Section: Prospective Applications Of Exchange-coupled Nanoparticlesmentioning
confidence: 99%
“…In addition to its potential spintronics applications [107,108], EB is an important tool in understanding fundamental nanoscale spin ordering, knowledge of which is essential to tailor the anisotropic magnetic properties of nanoparticle systems for potential rare-earth-free permanent magnet applications [109] and for biomedical applications such as magnetic hyperthermia [42,110,111,112] via a controllable exchange coupling mechanism. In particular, Lee et al have shown that the effective anisotropy can be tuned by using exchange-coupled core/shell nanoparticles (exchange anisotropy), which, in effect, increase the heating efficiency of MNPs [110].…”
Section: Prospective Applications Of Exchange-coupled Nanoparticlesmentioning
confidence: 99%
“…[27] In this regard, an exciting possibility is the fabrication of devices based on self-assemblies of exchange coupled core/shell MNPs with tailored magnetic properties. [28] The coercive field in these systems can be finely modified through the interface magnetic coupling [29][30][31][32][33][34], the core size and shell thickness, [35][36][37] or the magnetic anisotropy of the components. [23,[38][39][40] Devices of this type should provide a way to manipulate at will the characteristic switching field of TMR by controlling the magnetic coupling across the core/shell interface.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to enhance MS in hard-magnetic materials is the exchange coupling low-MS materials (e.g., BHF) with high-MS softmagnetic materials. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Actually, in recent years, there has been an increased interest in hard-soft-magnetic core/shell nanoparticles due to the large number of potential applications. 25 However, most of the studied systems have polycrystalline shells, which inevitably results in sub-optimal properties.…”
Section: Introductionmentioning
confidence: 99%